IMPLEMENTASI POMPA DC DAN FLOW METER PADA ALAT PENGISIAN BBM OTOMATIS (AUTO FILL) BERBASIS ARDUINO MEGA - Andika, Andika Rahman (Universitas Lambung Mangkurat, 2024)
Currently, the payment system for refueling vehicles in Indonesia still uses cash payments to gas station staff. Based on these problems, the researchers designed a prototype of an Arduino-based Mini Gas Station and e-TOLL. In this study only discusses the driving motor, dc pump, flow meter, and the time obtained. Research using the experimental method. The results of the study are that to carry out automatic petrol filling, a motor with high speed is needed. The results obtained during the test were that the DC pump motor had an average of 983.6 RPM, the voltage obtained was 5.2 Volts, and the required power was 50.2 watts. The time needed to fill a 1-10 liter tank is approximately 10 minutes according to the size of the tank. On a servo motor or automatic barrier that is used as a barrier gate, when it is finished refueling it will move to form 90° (up) and after the vehicle has passed the Loop Detector it will again form an angle of 0°. Keywords: DC Pump, Flow Meter, Auto Fill, Barrier Gate.